Refugees of Conflict, Casualties of Conjecture: The Trojan Horse Theory of Terrorism and its Implications for Asylum - Eybergen, Cory (Terrorism and political violence, 2022)
There are more displaced persons worldwide today than there ever has been before. Many countries, despite the urgent need for collective effort in providing for these persons, have been slow to accommodate them. Applicants continue to face stringent legal and practical barriers to asylum, even in countries party to the various international refugee agreements. Restrictions on applications are routinely justified with reference to national security, and in particular to defense against terrorism. There is a belief in some sectors of the polity and public that allowing greater numbers of refugees into the country will result in more incidences of violent terrorism. Refugee resettlement programs are caricatured as the Trojan horse permitting terrorists’ passage through national borders. Little has been done, empirically, that could testify to the veracity of such a theory, and that which has been done has been equivocal. Moreover, previous studies were unable to establish anything past a coincidental association between refugee populations and experiences of terrorism. This study explicitly tests the idea that refugees, by their own actions, cause terrorism. The findings of the study do not support Trojan horse or other theories that villainize refugees, nor are they decisive of a connection between refugees and terrorism.